Development and Investigation of Diagnostic Efficiency of a Test Kit for the Detection of IgM-antibodies to Individual Antigens of Rubella Virus by Immunoblotting (Western Blot) - S. G. Mardanly; A. S. Avdonina (Эпидемиология и вакцинопрофилактика)
Relevance. During serological diagnosis of rubella by enzyme immunoassay (detecting IgM), it is possible to obtain an indefinite or false-positive result. In this case, is needed an additional confirmatory test. It can be carried out by immune blotting, which allows detecting antibodies to specific rubella antigens. To date, in the Russian Federation, there is no such kit of reagents, which makes its development quite actual. Aim. The aim of this research was the development of a Russian test kit for detecting IgM-antibodies to individual rubella virus antigens by immune blotting (Western blot format). Materials and methods. Production of immunosorbent for a new test kit included electrophoresis of the native rubella virus lysate in a polyacrylamide gel to separate proteins by molecular weight and transfer (blotting) of separated proteins onto a nitrocellulose membrane. Investigation of sensitivity and specificity of the new test kit was carried with standard panels of serums containing and not containing IgM to the rubella virus, and with clinical samples characterized by the ELISA method. Results and its discussion. As a result of this work, was designed a Russian test kit that allowed detection IgM-antibodies to individual rubella virus antigens by immune blotting. This test kit has analytical sensitivity and specificity -100%, diagnostic sensitivity - at least 99.61% and diagnostic specificity - and at least 99-99%. The diagnostic efficiency is not less than 99.5%. Conclusion. The developed test kit has high rates of analytical and diagnostic sensitivity and specificity, as well as high diagnostic efficiency. It is intended for confirmatory research in the diagnosis of rubella infection.